Hepatitis B Virus Infection as a Risk Factor for Developing Diabetes Mellitus: A Meta-Analysis of a Large Observational Studies - Mutiara Nindya Sari; Clarissa Agdelina; Darlene Bahri; Nadya Regina Permata; Joue Abraham Trixie (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: There are a lot of theories about how Hepatitis B Virus (HBV) infection affects many diseases, one of them is Diabetes Mellitus (DM). However, the relation remains controversial between DM and HBV as an infection. This study aims to evaluate HBV infection as a risk factor for developing DM.Method: A systematic review was performed using medical search engines such as Pubmed, ScienceDirect and GoogleScholar. References until February 2021 that met the inclusion criteria were reviewed. The primary outcome was the prevalence of DM. Authors also perform Subgroup analyses based on study type. The extracted data were analyzed using RevMan 5.4 application.Results: A total of 20 studies were analyzed with 245,468,411 subjects included. In which divided into two groups, patients with HBV infected group and non infected HBV group. Authors found that there is a statistically difference between patients with HBV infected groups and non infected HBV groups on the primary outcome which is the prevalence of DM (OR 1.24; 95% CI, 1.10-1.41; p = 0.0006). Authors also found the same results based on study type both in case-control (OR = 1.76; 95% CI: 1.08-2.85; p = 0.02) and cross-sectional (OR = 1.40; 95% CI: 1.05-1.85; p = 0.02) studies. Meanwhile in Cohort studies the results show no statistically significant difference between the two groups (OR = 1.07; 95% CI: 0.87-1.33; p = 0.52). Conclusion:  HBV infected patients have a higher risk of developing DM than patients without HBV infection.